Companion of the 2023 ACM/IEEE International Conference on Human-Robot Interaction 2023
DOI: 10.1145/3568294.3580152
|View full text |Cite
|
Sign up to set email alerts
|

Who's in Charge?

Abstract: This paper presents a conceptual approach regarding robot-to-user adaptation, with a focus on the psychological effects of this adaptation process during human-robot interaction (HRI). This approach emphasizes the pertinent role of users in shaping adaptation processes. First, a literature review revealed perceived personal relevance as the central determinant of successful robot-to-user adaptation. Second, we distinguish two main types of adaptations which depend on the extent to which a user is involved: Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 90 publications
2
6
0
Order By: Relevance
“…In the presented research, we followed a user-centered approach while implementing and training two working memory architectures on an industrial RB-KAIROS + robot ( Robotnik Valencia, Spain, 2023 ): One of these architectures was based on GRU ( Cho et al, 2014 ), a commonly used state-of-the-art architecture, the other was based on WorkMATe ( Kruijne et al, 2021 ), a biologically-inspired alternative. Emphasizing the humans’ perspective on HRI, we considered potential users’ ideas and perceptions of robot navigation already before initiating the implementation and training processes as recommended by previous research (e.g., Mahmood et al, 2000 ; Ben Allouch et al, 2009 ; Schiffhauer et al, 2016 ; Bernotat and Eyssel, 2017a ; Diehl et al, 2017 ; Azamfirei et al, 2023b ; Psarommatis et al, 2023b ; Lacroix et al, 2023 ). This approach was innovative because, so far, only little attention has been paid to the humans’ perspective when robot working memory was implemented and trained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presented research, we followed a user-centered approach while implementing and training two working memory architectures on an industrial RB-KAIROS + robot ( Robotnik Valencia, Spain, 2023 ): One of these architectures was based on GRU ( Cho et al, 2014 ), a commonly used state-of-the-art architecture, the other was based on WorkMATe ( Kruijne et al, 2021 ), a biologically-inspired alternative. Emphasizing the humans’ perspective on HRI, we considered potential users’ ideas and perceptions of robot navigation already before initiating the implementation and training processes as recommended by previous research (e.g., Mahmood et al, 2000 ; Ben Allouch et al, 2009 ; Schiffhauer et al, 2016 ; Bernotat and Eyssel, 2017a ; Diehl et al, 2017 ; Azamfirei et al, 2023b ; Psarommatis et al, 2023b ; Lacroix et al, 2023 ). This approach was innovative because, so far, only little attention has been paid to the humans’ perspective when robot working memory was implemented and trained.…”
Section: Discussionmentioning
confidence: 99%
“…Involving potential users’ perceptions and preferences already in the research and development processes of new technologies was found to lead to more positive user experiences and safety in human-technology interaction (see Mahmood et al, 2000 ; Ben Allouch et al, 2009 ; Schiffhauer et al, 2016 ; Bernotat and Eyssel, 2017a ; Diehl et al, 2017 ; Robinson et al, 2020 ; Lacroix et al, 2023 ). Therefore, in the present research we addressed a research gap by putting the humans’ perspective into focus during the implementation and training of two working memory configurations on an industrial RB-KAIROS + robot ( Robotnik (Valencia, Spain) ): One working memory architecture was based on GRU ( Cho et al, 2014 ) and the other was based on WorkMATe ( Kruijne et al, 2021 ), the biologically-inspired alternative.…”
Section: Introductionmentioning
confidence: 99%
“…However, adaptation may likewise emphasize user involvement in the design of a robot. Consequently, adaptation is completely based on user decisions, i.e., customization [2], or hybrid forms that combine user involvement and system autonomy [3]. User involvement is often operationalized as a subjective feeling of selfinvestment in terms of time and effort, as well as a feeling of personal relevance and importance attached to a system [3]- [6].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, adaptation is completely based on user decisions, i.e., customization [2], or hybrid forms that combine user involvement and system autonomy [3]. User involvement is often operationalized as a subjective feeling of selfinvestment in terms of time and effort, as well as a feeling of personal relevance and importance attached to a system [3]- [6]. Such affective response may be elicited by actual user involvement, i.e., the objective dedication in terms of time and effort into the design of a product [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation